(untitled) (Sains Humanika, 2018)
Learning is a natural ability that every individual has. Ormrod, Anderman and Anderman (2017) explained that learning is a long-term change in mental representation and association from experience. For students, either school students or university students, they do not necessarily spend all their time to study. Students should be able to arrange their study time and leisure time well. This will allow them to learn more effectively. Interference between study and leisure is associated with motivation conflict in which individuals want to do something but at the same time, they need to do something else (Riediger & Freund, 2008), Thus, this analysis is conducted to identify the relationship between self-control, study-leisure interference and student well-being. Previous studies were obtained through online databases such as ScienceDirect, Springer Link and EBSCOHost. The finding shows that there is a correlation between self-control, study-leisure interference with the well-being of students. This is common issue among university students in Malaysia because most students are having difficult to manage their time properly. This will lead students to have workload and tend to putting off their tasks until the last minute.